2014
DOI: 10.1038/ismej.2014.167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals surprising divergence of two closely related strains of uncultivated UCYN-A cyanobacteria

Abstract: Marine planktonic cyanobacteria capable of fixing molecular nitrogen (termed 'diazotrophs') are key in biogeochemical cycling, and the nitrogen fixed is one of the major external sources of nitrogen to the open ocean. Candidatus Atelocyanobacterium thalassa (UCYN-A) is a diazotrophic cyanobacterium known for its widespread geographic distribution in tropical and subtropical oligotrophic oceans, unusually reduced genome and symbiosis with a single-celled prymnesiophyte alga. Recently a novel strain of this orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 64 publications
10
103
0
Order By: Relevance
“…This is in agreement with a greater contribution of B. bigelowii reads in the 0.8-5 μm size fraction (as compared with the 5-20 μm fraction) in the Tara-Oceans metabarcoding data analyzed here, as well as of UCYN-A2 reads in the same smaller size fraction in metagenomic samples of the South Atlantic (Cornejo-Castillo et al, submitted). The hypothesis about the obligatory dependence of UCYN-A with its host (Tripp et al, 2010;Thompson et al, 2012;Bombar et al, 2014) has been recently reinforced with the strong coupling observed in the transfer of carbon and nitrogen metabolites between partner cells (Krupke et al, 2014b). On the other hand, the possibility of a freeliving population of the host could not be evaluated as the FISH probe used in previous studies (Krupke et al, 2014a) targeted the whole prymnesiophyte assemblage and not the specific host phylotypes.…”
Section: Discussionmentioning
confidence: 94%
“…This is in agreement with a greater contribution of B. bigelowii reads in the 0.8-5 μm size fraction (as compared with the 5-20 μm fraction) in the Tara-Oceans metabarcoding data analyzed here, as well as of UCYN-A2 reads in the same smaller size fraction in metagenomic samples of the South Atlantic (Cornejo-Castillo et al, submitted). The hypothesis about the obligatory dependence of UCYN-A with its host (Tripp et al, 2010;Thompson et al, 2012;Bombar et al, 2014) has been recently reinforced with the strong coupling observed in the transfer of carbon and nitrogen metabolites between partner cells (Krupke et al, 2014b). On the other hand, the possibility of a freeliving population of the host could not be evaluated as the FISH probe used in previous studies (Krupke et al, 2014a) targeted the whole prymnesiophyte assemblage and not the specific host phylotypes.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have questioned the bifurcating history of the tree of life, due to genetic exchange via lateral gene transfer (LGT; Ochman et al 2000;Kunin et al 2005). Yet, even though LGT can occur, as shown for example at threonyl tRNA synthease (Zhaxybayeva et al 2006), ribosomal genes seem to be rather conserved (Schirrmeister et al 2012) and large-scale multi-gene phylogenetic analyses have improved our understanding of cyanobacteria and reconstructed the phylum's history with increased statistical support for deep-branching (Shih et al 2013;Bombar et al 2014;Sanchez-Baracaldo et al 2014;Schirrmeister et al 2015).…”
Section: Phylogenetic History Of Cyanobacteriamentioning
confidence: 99%
“…As reported earlier, the genomes of UCYN-A1 and UCYN-A2 are similar in size, content, and streamlining (Bombar et al, 2014); while the DDA symbiont draft genomes differ largely (Figure 1, Table 1), and content appears influenced by the symbiont location (Hilton et al, 2013).…”
Section: Symbiont Genome Comparisonmentioning
confidence: 59%
“…The prymnesiophyte-UCYN-A symbioses are small in comparison; both hosts and symbionts are <10 µm. In fact a closer examination at the size fractionation experiments reported in Tripp et al (2010) (Figure 4, Tripp et al, 2010), demonstrates Villareal, 1992;Foster and Zehr, 2006;Foster and O'Mullan, 2008;Zehr et al, 2008;Tripp et al, 2010;Thompson et al, 2012Thompson et al, , 2014Hagino et al, 2013;Hilton et al, 2013;Krupke et al, 2013;Bombar et al, 2014;Hilton, 2014;Cabello et al, 2016;Cornejo-Castillo et al, 2016;Martínez-Pérez et al, 2016. √ up to 13 species are reported for Rhizosolenia-R. intracellularis symbioses hence we report the two most common.…”
Section: Methodological Biases: Un-quantified and Under-sampled Dispamentioning
confidence: 99%
See 1 more Smart Citation